Spatial analysis of soil erosion vulnerability in the Mandovi River watershed, India, using RUSLE and geospatial techniques - Gawas, Roshna; Kerkar, Pravina; Sawant, Sushant (Journal of Degraded and Mining Lands Management, 2025)
The current study aimed to estimate potential soil loss in the Mandovi River watershed using the Revised Universal Soil Loss Equation (RUSLE) model and geospatial techniques. The Mandovi Basin, a tropical coastal region in India with a drainage area of 2,047 km², experiences significant soil erosion. To achieve this, key RUSLE factors, including rainfall erosivity (R factor), soil erodibility (K factor), topographic factors (LS factor), cover management (C factor), and conservation practices (P factor), were obtained from satellite-based datasets. Thematic layers associated with all five RUSLE factors were developed through Geographic Information System (GIS) techniques. ArcGIS software was used to merge these layers and create the final soil erosion map of the watershed. The results revealed that soil loss within the Mandovi watershed varies between 0 and over 50 t ha?¹ yr?¹ with a mean value of 14.2 t ha?¹ yr?¹. Based on the calculated soil loss risk rates, the watershed was classified into five erosion severity classes: very high, high, moderate, low, and very low erosion risk. The findings indicate that approximately 52.42% of the Mandovi watershed falls under a very low risk of erosion, while a relatively small portion, around 5.28%, is exposed to a very high risk of erosion. The factors contributing to the high rate of erosion in the study area are the presence of barren land, steep terrain, high rainfall erosivity, and lack of adequate soil conservation measures. Identifying soil loss in the Mandovi watershed will support sustainable management of land and water resources.